N.I. Vorobyev’s contribution to the zoning of ethnographic groups of the Chuvash (according to ethnography) - Georgy B. Matveev (Историческая этнология)
N.I. Vorobyev made a great contribution to the comparative study of the history of settlement and traditional culture of the ethnographic groups of the Chuvash, their interethnic interaction with the contacted ethnoses. He identified three ethnographic complexes based on the features, both those that had archaic signs and newly formed ones. Regarding the history of the formation of ethnographic groups, the researcher argued that the population of the north-east of the Chuvash Volga region perceived more southern Turkic influences in their everyday life, began to differ in language and way of life from the north-western population, although they retained commonality with it in the main elements of language, culture and lifestyle. His conclusion that the main ethnographic groups of the Chuvash, as he considered the upper Viryal and lower Anatri, were finally formed during the 15th century in the northern regions of Chuvashia as a result of the rapprochement of the indigenous population of these areas with newcomers from the south, cannot be considered justified. The work of ethnographic expeditions in the Chuvash regions in the late 1940s and early 1950s, she showed that the archaic complex was most characteristic of the costume of the middle-aged Chuvash Anat enchi, although N.I. Vorobyev considered them an average or mixed ethnographic group. In general, he represented that group as part of the Anatri, who changed their way of life under the influence of borrowing from the Tatars. The author’s team, under the guidance of the scholar, developed in detail the classification of the Chuvash into groups and subgroups based on folk costume. N.I. Vorobyev for the first time identified three subgroups as part of anatri. The border zone between Anatri and anat yenchi, which was not clearly defined by its predecessors, in particular G.I. Komissarov, N.I. Vorobyev, was also not resolved. The riding costume was formed as a result of interaction with the mountain Mari people, although many features that unite it primarily with the anat Enchi costume were not replaced in it. The authors emphasise that the striking external differences that were recorded in the riding Chuvash northwestern subgroups and grassroots chuvashki hirti. They did not violate the common cultural community of the Chuvash people. It should be noted that the task of a more detailed substantiation of cultural and linguistic areas at the level of subgroups within the ethnographic groups of the Chuvash, divided into four subgroups in the upper zone and three in the middle and lower ones, unresolved by the expeditions of the late 1940s – early 1950s, remains relevant.